2018
DOI: 10.1108/ijssp-09-2017-0113
|View full text |Cite
|
Sign up to set email alerts
|

Meandering rides of the Swedish taxi industry

Abstract: Purpose The purpose of this paper is to study the interplay between changes in policies, rules and regulations that have altered ethnic composition and incomes in the Swedish taxi industry since deregulation in the 1990s. Design/methodology/approach This is a mixed-methods study, combining the qualitative interviews, scrutiny of relevant policy documents and statistical data of the Swedish population between 1992 and 2012. The analysis uses a mixed embeddedness perspective to show how the changed regulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Quantitative studies have frequently used the Global Entrepreneurship Monitor (Schott, 2018;Von Bloh et al, 2019;Ashourizadeh et al, 2020), some national surveys (e.g. Longitudinell integrationsdatabas för Sjukförsäkrings-och Arbetsmarknadsstudier, British Beyond embedded or not embedded important advantage of using mixed methods is to yield comprehensive knowledge about the focal phenomenon (Slavnic and Urban, 2018). Moreover, while the quantitative part gives the study scope, the qualitative part provides rich insights into the internal dynamics (Guell, 2016).…”
Section: Beyond Embedded or Not Embeddedmentioning
confidence: 99%
“…Quantitative studies have frequently used the Global Entrepreneurship Monitor (Schott, 2018;Von Bloh et al, 2019;Ashourizadeh et al, 2020), some national surveys (e.g. Longitudinell integrationsdatabas för Sjukförsäkrings-och Arbetsmarknadsstudier, British Beyond embedded or not embedded important advantage of using mixed methods is to yield comprehensive knowledge about the focal phenomenon (Slavnic and Urban, 2018). Moreover, while the quantitative part gives the study scope, the qualitative part provides rich insights into the internal dynamics (Guell, 2016).…”
Section: Beyond Embedded or Not Embeddedmentioning
confidence: 99%
“…This varied perception of regulation around the world has led to deregulation in different ways and to differing degrees. For example, New Zealand (1989), Sweden (1990) and the Netherlands (2000) all deregulated their taxi markets [4,50]. Elsewhere, it is common to see taxis (in the sense of vehicles that can be hailed on street) treated differently from private hire vehicles (PHV) which must be booked in advance of a journey, something which until recently tended to happen through despatch centres.…”
Section: The Taxi/private Hire Market Before and Since Ubermentioning
confidence: 99%
“…Though the evidence is limited, a systematic review by Sterud et al (2018) focused on working conditions and occupational health among immigrants in Europe and Canada concluded that, more often than natives, immigrants experience precarious employment that is negatively correlated with health. Especially non-Western immigrants are more prone to work in low-skilled and lower-paid jobs (Behtoui et al, 2020;Ilsøe, 2016;Slavnic & Urban, 2018) with physical demanding work tasks (Dunlavy and Rostila 2013). Further, work-related factors may have a detrimental effect on health, such as the segregation of lower-educated immigrants into lower-paid jobs with poorer job security and working conditions compared to native workers (Taloyan et al, 2019;Charlesworth & Malone, 2022;Hussein, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the native-immigrant gap in sickness absence is believed to stem from immigrants' disadvantages in their work situations relative to natives. Poor host country human capital, such as language, formal skills, and work-relevant experience, has been put forward as a possible explanation for immigrants' difficulties in entering the labour market (Shields and Price 2002;Chiswick & Miller, 2010) and thus, a selection into low-skilled and physically demanding jobs with less autonomy (Behtoui et al, 2020;Dunlavy and Rostila 2013;Ilsøe, 2016;Shields and Price 2002;Slavnic & Urban, 2018) that adversely affect their health (Sterud et al, 2018). Long-term exposure to demanding and stressful working conditions may affect poor health (Fletcher et al 2011), as theorised in Karasek's (1979) demandcontrol model, which has been used to explain such differences, where demand and lack of control in the work situation cause poor health.…”
Section: Introductionmentioning
confidence: 99%